From Existential to Social Understandings of Risk: Examining Gender Differences in Nonreligion. (December 2017) - Edgell, Penny; Frost, Jacqui; Stewart, Evan
Across many social contexts, women are found to be more religious than men. Risk preference theory proposes that women are less likely than men to accept the existential risks associated with nonbelief. Building on previous critiques of this theory, we argue that the idea of risk is relevant to understanding the relationship between gender and religiosity if risk is understood not as existential, but as social. The research on existential risk focuses on religious identification as solely a matter of belief; as part of the movement away from this cognitivist bias, we develop the concept of social risk to theorize the ways that social location and differential levels of power and privilege influence women's nonreligious choices. We show that women's nonreligious preferences in many ways mirror those of other marginalized groups, including nonwhites and the less educated. We argue that nonreligion is socially risky, that atheism is more socially risky than other forms of nonreligion, and that women and members of other marginalized groups avoid the most socially risky forms of nonreligion.